Efektivitas Senam Ergonomis dan Kompres Hangat Rebusan Serai Terhadap Skala Nyeri Sendi pada Penderita Asam Urat di Desa Alassumur Lor - Kholifatur Rizqiyah; Ainul Yaqin Salam; Alwin Widhiyanto (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Gout is a condition where high levels of uric acid in the blood that causes pain, and pain in the joints. One of the measures to lower joint pain is non- pharmacologically with ergonomic Gymnastics and warm compresses of lemongrass decoction. The purpose of this study is to analyze the effectiveness of ergonomic gymnastics and warm compresses of lemongrass decoction on the scale of joint pain in patients with gout in Alassumur lor village. This type of research was quasi-experimental with cross over group design approach. A population was 38 people selected by purposive sampling technique obtained 34 respondents who meet the inclusion requirements. This research used the numeric pain scale (NRS) observation sheet Instrument. The normality of the data had been tested with Kolmogorov-smirnov. The results of the study obtained ergonomic gymnastics pain scale period I pre-test was 6.94 and post-test was 2.94, stew period II pre-test was 5.18 post-test was was 2.59. In the warm compress group lemongrass stew period I pre-test was 3.18, post-test 1.82, period II pre-test was 3.76, post-test was 1.94. The results of data analysis obtained the value of pV 0.000 with a significant level of p value <a = 0.005, the value of Z prepost period I ergonomic exercise -3.695, warm compress of lemongrass stew -3.676, in period II ergonomic exercise -3.580 and warm compress lemongrass stew -3.531, so that it can be stated that ergonomic exercise is more effective to decrease the joint pain scale in patients with gout in Alassumur lor village. Ergonomic Gymnastics turns out to be more effective to reduce joint pain in gout and is expected to be one of the alternative interventions to reduce joint pain in people with gout.